Long-term functional outcomes in patients with isolated cerebellar infarction: the KOSCO study - Ho Seok Lee; Min Kyun Sohn; Jongmin Lee; Deog Young Kim; Yong-Il Shin; Gyung-Jae Oh; Yang-Soo Lee; Min Cheol Joo; So Young Lee; Min-Keun Song; Junhee Han; Jeonghoon Ahn; et al. (Frontiers in Neurology)
BackgroundThere are relatively few reports on the long-term sequential functional recovery and prognosis in patients with cerebellar infarction. The aim of this study was to investigate the long-term recovery of multifaceted functional outcomes up to 36 months after onset and the functional prognosis of isolated cerebellar infarction.MethodsThis study was a retrospective analysis of the Korean Stroke Cohort for Functioning and Rehabilitation (KOSCO) data up to 36 months after onset. Isolated cerebellar infarction was defined as the presence of lesions in the cerebellum without lesions in other brain parenchyma. We assessed multifaceted functional domains, including motor (Fugl-Meyer Assessment, FMA), ambulatory (Functional Ambulation Category, FAC), cognitive (Korean Mini-Mental State Examination, K-MMSE), swallowing (American Speech-Language-Hearing Association National Outcome Measurement System Swallowing Scale, ASHA-NOMS), and language functions (Short version of the Korean Frenchay Aphasia Screening Test, Short K-FAST), using serial measurements. In addition, functional outcome was assessed with the Functional Independence Measure (FIM) up to 36 months after onset.ResultsAmong 390 screened isolated cerebellar infarction patients, a total of 183 patients were included in this study. Cognitive (mean[SD] of K-MMSE 27.6 ± 3.6) and swallowing (ASHA-NOMS 6.8 ± 0.7) functions showed significant improvement up to 3 months (p < 0.05). Motor (FMA 98.8 ± 3.8) and language (ASHA-NOMS 6.9 ± 0.4) functions improved significantly up to 6 months (p < 0.05). Furthermore, ambulatory function (FAC 4.7 ± 0.9) and functional independency (FIM 122.2 ± 12.0) continued to improve up to 12 months (p < 0.05). Vascular territory involving superior cerebellar artery, older age, female sex, and greater initial severity were identified as negative independent prognostic factors predicting functional outcome measured by FIM at 12 months after stroke.ConclusionThe plateau of recovery in multifaceted functional outcomes varied among patients with cerebellar infarction. Functional independence plateaued at 12 months and showed a relatively favorable prognosis up to 36 months after stroke.